Selected decisions and selected documents of the International Monetary Fund - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The book contains the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the International Monetary Fund, as well as selected documents, to which frequent reference is made in the current activities of the Fund.
Some issues have accompanying annex volumes.
includes index
usc 02/06/17; 09/06/17
Loans
Keywords: International finance; IMF; Internationale financiën.; International finance - IMF